Answer:
Options (2), (4) and (5)
Explanation:
Option 1
(3x + 14 - x + 112) and (4x + 134)
Since, (3x + 14 - x + 112) = (3x - x) + (12 + 112)
= 2x + 124
Therefore, (3x + 14 - x + 112) ≠ (4x + 134) [Not equivalent]
Option 2
(2 + 6x) and 2(3x + 1)
2(3x + 1) = (6x + 2)
Therefore, (2 + 6x) = (6x + 2) [Equivalent]
Option 3
3(x + 1) - (1 - x) and (2x + 3)
Since, 3(x + 1) - (1 - x) = 3x + 3 + x - 1
= (3x + x) + (3 - 1)
= 4x + 2
Therefore, (2x + 3) ≠ (4x + 2) [Not equivalent]
Option 4
3x and 4(x + 1) - x - 4
Since, [4(x + 1) - x - 4] = 4x + 4 - x - 4
= (4x - x) + (4 - 4)
= 3x
Therefore, 3x = [4(x + 1) - x - 4] [Equivalent]
Option 5
(5.5 + 2.2x + 3.8x - 4.1) and (1.4 + 6x)
Since, (5.5 + 2.2x + 3.8x - 4.1) = (2.2x + 3.8x) + (5.5 - 4.1)
= (6x + 1.4)
Therefore, (1.4 + 6x) = (6x + 1.4) [Equivalent]